Development of a choco-coco milk drink - Baltazar, Hazel Marie Laurente; Quijano, Ana Marie M. (1998., 1998)
Milk beverages are refreshing sources of much needed nutrients such as proteins and fat. However, the country cannot supply sufficient amount of milk and milk products due to its sizable cattle industry. As a result, other sources of proteins and fat are being utilized. The study dealt with the development of a substitute milk beverage utilizing coconut milk. It was divided into two stages: the first stage involved the procurement and preparation of raw materials as well as the extraction of coconut milk. The second stage was divided into four phases. In the first phase, the optimum ratio of milk solid and fat to coconut milk was determined. A ratio of 75:25% milk solid and fat to coconut milk was found to be optimum. Phase II involved the determination of the optimum level of the cocoa powder. A 2% level of cocoa powder was found to be optimum in the third phase. In the fourth phase, the formulation and process was standardized. Sensory evaluation, physico-chemical and microbial analyses were done to evaluate the quality of the trial samples. The average protein and fat content were 1.49% and 5% respectively. The average total solids was 20.50% The total soluble solids was 11.67°Bx on the average. The viscosity, on the other hand, was 200 centipiose. It was compared to the fat and protein content of a leading pasteurized chocolate milk. The fat content was higher by 1% while the protein content was lower by 5.51%. The total soluble solids was lower by 6.13%. A cost analysis for the production of 5000 ml was conducted. Total cost for the production was P152.59 such that with a 10% mark-up, a 250 ml sample would cost P8.38 whcih is lower than the leading pasteurized chocolate milk by P6.12.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Beverages